Safe and Ultraconservative Rehabilitation of Worn Teeth Patients: How Sectional Clear Aligners May Enhance the Prosthetic Treatment Plan - Camillo D’Arcangelo; Mirco Vadini; Matteo Buonvivere; Francesco De Angelis (Case Reports in Dentistry)
This study describes the clinical workflow for occlusal vertical dimension (OVD) increase in patients showing extensive tooth wear and mild teeth misalignment/crowding. A patient affected by dental erosion and occlusal abnormalities was treated to improve her situation. After ascertaining sound condyle and temporomandibular joint (TMJ) conditions, an OVD increase was sought to provide enough inter-occlusal space for the restorations. The use of TMJ three-dimensional imaging throughout the clinical procedures allowed to objectively track the condyle and disk position and confirm a steady condyle–glenoid cavity relationship before definitive restorations placement. Sectional clear aligner therapy prior to totally additive prosthetic rehabilitation allowed obtaining slight derotation and movements of anterior teeth, thus maximizing sound tissue preservation. Adhesively luted restorations were finally delivered on both anterior and posterior sectors. At the end of the treatment, the pre-operative TMJ balance appeared successfully preserved, and the patient was satisfied with the aesthetic and function achieved.